Teaching Corporations Law from a Transactional Perspective and Through the Use of Experiental Technique - Andrew Godwin (Legal Education Review)
Law Schools throughout the Commonwealth face increasing pressure to attract international students for postgraduate study. This paper focuses on the taught LLM program, which in many Law Schools will account for the largest enrolment of postgraduate students. Some views will be advanced regarding the international dimensions of legal education and its significance in marketing an LLM by coursework. There are several strands to the enquiry. First, it must be asked: who are the lead players, and why? A significant factor is a Law School’s reputation and international ranking. There is a selfperpetuating synergy between institutions of similar reputation and standing. Such entities have greater leverage in negotiating academic alliances and student focused schemes, as well as attracting external funding and philanthropy. This leads to the principal research question: what are the elements for a successful LLM programme, both generally, and for universities that do not enjoy the same cachet and operate with limited resources? This will be analysed from a comparative perspective, recognising that Law Schools are functioning in an increasingly competitive global market.